2023
DOI: 10.46729/ijstm.v4i1.697
|View full text |Cite
|
Sign up to set email alerts
|

Customer-Based Brand Equity, Company Reputation and Product Quality Effect on Customer Loyalty: Air Conditioner Retail Market in Medan

Abstract: This research explores and focuses on customer perceptions, because there is still a lack of research in knowing the relationship between customer perceptions of products and retail stores. Data collection by interviews, questionnaires, and observations on Panasonic AC retail customers. This study tries to examine the influence of the dimensions of customer loyalty which are influenced by the dimensions of Customer Based Brand Equity (CBBE), Company Reputation and Product Quality. This research is associative,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 30 publications
1
0
0
Order By: Relevance
“…The results of this study support the research of Suwarno et al, (2023); Afridita & Rahmidani, (2022); Chalirafi et al, (2021);and Alwi et al, (2017), which found that company reputation has a significant positive effect on loyalty.…”
Section: The Effect Of Company Reputation On Loyaltysupporting
confidence: 88%
“…The results of this study support the research of Suwarno et al, (2023); Afridita & Rahmidani, (2022); Chalirafi et al, (2021);and Alwi et al, (2017), which found that company reputation has a significant positive effect on loyalty.…”
Section: The Effect Of Company Reputation On Loyaltysupporting
confidence: 88%